2021
DOI: 10.7150/ijbs.56800
|View full text |Cite
|
Sign up to set email alerts
|

Genistein-3′-sodium sulfonate Attenuates Neuroinflammation in Stroke Rats by Down-Regulating Microglial M1 Polarization through α7nAChR-NF-κB Signaling Pathway

Abstract: Microglial M1 depolarization mediated prolonged inflammation contributing to brain injury in ischemic stroke. Our previous study revealed that Genistein-3′-sodium sulfonate (GSS) exerted neuroprotective effects in ischemic stroke. This study aimed to explore whether GSS protected against brain injury in ischemic stroke by regulating microglial M1 depolarization and its underlying mechanisms. We established transient middle cerebral artery occlusion and reperfusion (tMCAO) model in rats and used lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Furthermore, GSS can upregulate α7nAChR expression to inhibit the NF-κB pathway, decrease the number of M1 microglia, and inhibit neuroin ammation in tMCAO rats [14,15]. In this study, we found that GSS signi cantly reduces the cerebral infarct volume of HIE neonatal rats, which we suspect is a promising pharmacological agent to treat HIE, but its molecular target is still unknown.…”
Section: Introductionmentioning
confidence: 59%
“…Furthermore, GSS can upregulate α7nAChR expression to inhibit the NF-κB pathway, decrease the number of M1 microglia, and inhibit neuroin ammation in tMCAO rats [14,15]. In this study, we found that GSS signi cantly reduces the cerebral infarct volume of HIE neonatal rats, which we suspect is a promising pharmacological agent to treat HIE, but its molecular target is still unknown.…”
Section: Introductionmentioning
confidence: 59%
“…When NF-κB is activated, it is phosphorylated and translocates to the nucleus, where it mediates in ammatory brain injury by inducing the transcription of many proin ammatory genes, such as IL-1β and TNF-α (Zhang et al, 2019). In vivo, genistein-3′-sodium sulfonate, a structural modi er of the phytoestrogen genistein, was shown to inhibit the activation and nuclear translocation of NF-κB and reduce the M1 polarization of microglia, thereby inhibiting neuroin ammation in tMCAO rats (Liu et al, 2021). Multiple in vitro studies have also demonstrated that NF-κB is involved in microglial activation and M1 polarization (Kong et al, 2022;Liu et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The rat tMCAO model was constructed by the modi ed Zea Longa suture method as described previously (Li et al, 2017;Liu et al, 2021;Shan et al, 2021). Rats were anesthetized by intraperitoneal injection of 1% pentobarbital sodium at a dose of 4.5 mL/kg.…”
Section: Transient Middle Cerebral Artery Occlusion (Tmcao) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In models of ischemia, STVNA has been implicated in inhibition of astrogliosis [ 210 ], modulation of microglia/macrophage polarization [ 211 ], and preservation of volume control in endothelial cells [ 212 ]. Flavonoids constitute a class of natural products with a significant role in the inhibition of microglial polarization and management of oxidative stress, with a number of compounds acting upon the NF-κB signaling pathway [ 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 ]. A number of the flavonoids have been implicated in the activity of stem cells, including hesperetin in NSC proliferation [ 221 ], icariin in neurogenesis and angiogenesis through release of BDNF and VEGF [ 222 ], and quercetin in enhancing stem cell viability and proliferation while reducing apoptosis [ 223 ].…”
Section: Current Nrf2-directed Treatment Modalitiesmentioning
confidence: 99%